New Clause in Bank Credit Agreement in Relation to Consumer Protection Act (Study on PT. Bank Negara Indonesia, Tbk. Denpasar Branch) - Komang Yustika Dewi Suryaningsih; A.A.A. Ngr. Tini Rusmini Gorda (Jurnal Hukum Prasada, 2021)
Credit agreement in standard form which is being made unilaterally by the bank until present is still becoming a special legal issue in agreement field of civil law. In addition, viewed from the side of the agreement it is also against consumer protection law as set in Consumer Protection Act. Problem formulation of is divided into namely regarding the existence of standard clause in bank agreement if associated with Article 18 of Consumer Protection Act and legal consequence of standard clause in credit agreement associated with consumer protection. This study aims to identify the presence of standard clause in banking agreement if related with Article 18 of Consumer Protection Act and legal consequence to the standard clause in credit contract is associated with consumer protection. The research is a juridical empirical. The location is on PT. Bank Negara Indonesia in Denpasar city. The author is guided by laws and regulations related with public fact, that is first problem formulation is analyzed from balancing principle and next the second problem formulation is from consumer protection theory. The result shows that the implementation of the provision tends to protect the bank as businesses. Moreover, the legal consequence of Bank BNI’s credit contract which does not meet the provision will result in null and void.